2019
DOI: 10.1093/jac/dky530
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antimicrobial therapy on the gut microbiome

Abstract: The gut microbiome is now considered an organ unto itself and plays an important role in health maintenance and recovery from critical illness. The commensal organisms responsible for the framework of the gut microbiome are valuable in protection against disease and various physiological tasks. Critical illness and the associated interventions have a detrimental impact on the microbiome. While antimicrobials are one of the fundamental and often life-saving modalities in septic patients, they can also pave the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(133 citation statements)
references
References 107 publications
6
118
0
1
Order By: Relevance
“…The importance of these bacterial groups as potential barriers or facilitators for antibiotic-induced bacterial community rearrangements may deserve further investigation. In general, the PCA results ( Figure S1) are in agreement with the literature that suggests that the oral or intravenous antibiotic administration can promote the disturbance of the human gut microbiome (Bhalodi et al, 2019;Francino 2016). The PCA analysis ( Figure S1) suggests that the significant variations observed in Proteobacteria relative abundance (Table S3), might be due to complex fecal bacterial community rearrangements rather than to the increase or decrease of a specific bacterial lineage.…”
Section: Effect Of Incubation Condition On the Microbial Community Cosupporting
confidence: 87%
“…The importance of these bacterial groups as potential barriers or facilitators for antibiotic-induced bacterial community rearrangements may deserve further investigation. In general, the PCA results ( Figure S1) are in agreement with the literature that suggests that the oral or intravenous antibiotic administration can promote the disturbance of the human gut microbiome (Bhalodi et al, 2019;Francino 2016). The PCA analysis ( Figure S1) suggests that the significant variations observed in Proteobacteria relative abundance (Table S3), might be due to complex fecal bacterial community rearrangements rather than to the increase or decrease of a specific bacterial lineage.…”
Section: Effect Of Incubation Condition On the Microbial Community Cosupporting
confidence: 87%
“…new for scientists and physicians, more than 50,000 full-text articles on microbiota, including the results of randomized double-blind trials, are now available online through the PubMed query. The papers not only deal with the microbiota composition in various diseases, but also frequently address the global significance of its metabolic activity, its relation to antimicrobial therapy, complications, and adverse outcomes [68][69][70][71][72][73][74][75][76][77][78][79].…”
Section: постулат второй микробиота и митохондрии человека функционаmentioning
confidence: 99%
“…Enterobacterales order of Proteobacteria [55][56][57][58][59][60][61]. Of the eleven subjects, all but Subject I were 134 female and all but Subject G were white.…”
Section: Overview Of Subjects 123mentioning
confidence: 99%
“…suggested that levofloxacin has a relatively minor impact on the gut microbiome, primarily 370 reducing levels of Enterobacterales [55][56][57][58][59][60][61], and it may be less-associated with Clostridiodes difficile-associated diarrhea outbreaks than other antimicrobials, including other 372 fluoroquinolones [138]. 373…”
Section: Prediction Of Arg Density From Species Abundances 317mentioning
confidence: 99%
See 1 more Smart Citation